Distribution and Allele Frequencies of ABO and Rh Blood Types in Al-Jabal Al-Akhdar, Libya - Aljebali, Ahmad; Sulaiman, Nisreen (AlQalam Journal of Medical and Applied Sciences, 2026)
This study investigates the distribution and allele frequencies of the ABO and Rh blood systems in the Al-Jabal Al-Akhdar region of Libya. A total of 3,363 individuals from ten towns in the region were included. ABO blood types and Rh factor were recorded from families, and ABO genotypes were inferred by pedigree analysis. Chi-square goodness-of-fit tests were used to compare the proportions of observed ABO phenotypes and Rh antigens across towns. Overall, blood type A had the highest frequency at 33.37%, followed by O at 29.63%, B at 27.92%, and AB at 9.09%. Regarding Rh status, 88.91% of individuals were Rh-positive, and 11.09% were Rh-negative. Allele frequencies for the ABO system in the overall population were estimated as p = 0.280, q = 0.242, and r = 0.478. The allele frequencies of the Rh system were p = 0.766 and q = 0.234. Significant differences across towns were observed for blood types A, AB, and O (p-value = 0.025, 0.000, and 0.001, respectively). However, no significant differences were found for blood types B, Rh-positive, and Rh-negative (p-value = 0.301, 0.990, and 0.093, respectively) across towns. These findings provide useful data for population genetics and transfusion medicine in the region. Further work is needed to examine genetic diversity and population structure in other blood group systems.